Understanding the contradiction between rural poverty and rich cultivated land resources: A case study of Heilongjiang Province in Northeast China. (September 2021) - Li, Dongmei; Yang, Yuanyuan; Du, Guoming; Huang, Shanlin
Abstract: Although the global population living in extreme poverty steadily decrease, poverty is still a common problem faced by mankind. Understanding the spatial characteristics of poverty and its interaction with land use strategies is an essential prerequisite for formulating poverty reduction strategies and achieving rural revitalization. According to the spatial poverty theory, insufficient geographical capital is a well acknowledged precondition for the spatial agglomeration of rural poverty, however there are few researches on the regional contradictory phenomenon that the richer the arable land resources are, the poorer the rural areas are. Based on the spatial data and social-economic statistical data, the spatial analysis combined with Geographical detector were adopted in this study to depict the spatial consistency between rural poverty and arable land enrichment, then analyze the formation mechanism of the rural poverty in Heilongjiang Province. Results showed that the spatial distribution of rural poverty in Heilongjiang Province was clustered in regions with rich cultivated land resources, and jointly affected by quantitative factors, qualitative factors and locational conditions of cultivated land. However, there were significant spatial differences in the action mode and force magnitude of various cultivated land factors on the poverty space. We found that the quantitative abundance of cultivated land resources couldn't always alleviate rural poverty in the plain agricultural areas, and the disadvantages of quality and location of cultivated land might increase the incidence of poverty of agriculture-dependent families. When formulating regional targeted poverty alleviation policies, the influence of cultivated land quality and location conditions on agricultural family welfare should be taken seriously, as same as the quantity of cultivated land. The findings of this research will provide scientific basis and reference for regional sustainable poverty reduction and rural revitalization. Highlights: There was a spatial correlation between the incidence of rural poverty and the enrichment degree of cultivated areas. Effects of the influencing factors of cultivated land on poverty space were quite different in various subregions. The quantitative abundance of cultivated land resources does not necessarily to alleviate rural poverty. Disadvantages of quality and location of cultivated land could increase the poverty of agriculture-dependent families. Attributes of geographic capital should be considered systematically when formulating targeted poverty alleviation policies.